Relación de parvovirosis con pancreatitis en perros atendidos en la clínica veterinaria “Super Can” de la ciudad de Machala 2024. - Gallegos Suárez, Carola Anabel (Machala : Universidad Técnica de Machala, 2024)
This research focuses on exploring the possible relationship between parvovirus and pancreatitis in dogs, specifically those treated at the ""Super Can"" veterinary clinic in Machala. Both diseases, parvovirus and pancreatitis, pose significant challenges to canine health, and their interrelationships are of interest and debate in the veterinary community. The 40 sampled patients with gastrointestinal signs underwent an immunochromatography test to detect canine parvovirus, with 23 testing positive for canine parvovirus. This data was recorded on an anamnesis sheet. Canine pancreatic lipase was evaluated along with pancreatic ultrasound description, where 5 variables were assessed: pancreatic size, pancreatic echogenicity, echotexture, echogenicity of the surrounding mesentery, and peripancreatic fluid. Once all the data were obtained, they were subjected to statistical tests such as Chi-Square and Fisher's exact test for small samples to determine the relationship between parvovirus and pancreatitis in the 23 dogs. The results showed that there is no statistical significance. In conclusion, with the current data, there is not enough evidence to assert a significant relationship between both diseases in this specific population. These findings underscore the importance of further research to elucidate the relationship between both diseases, as well as their diagnostic and therapeutic implications in veterinary clinical practice. They also highlight the need for active surveillance and an integrated approach in managing these pathologies to improve the health and well-being of canine patients.
"Esta investigación se enfoca en explorar la posible relación entre la parvovirosis y la pancreatitis en perros, específicamente aquellos atendidos en la clínica veterinaria ""Super Can"" de Machala. Ambas enfermedades, la parvovirosis y la pancreatitis, representan desafíos significativos para la salud canina y sus interrelaciones son objeto de interés y debate en la comunidad veterinaria. Los 40 pacientes muestreados con signos gastroentéricos se les realizó prueba de inmunocromatografía para detectar parvovirosis canina, 23 positivos a parvovirosis canina, estos datos fueron registrados en una hoja de anamnesis, se evaluaron lipasa pancreática canina junto con la descripción ecográfica pancreática donde se evaluó 5 variables: tamaño pancreático, ecogenicidad del páncreas, ecotextura, ecogenicidad del mesenterio circundante y líquido peripancreático. Una vez obtenidos todos los datos se sometieron a una prueba estadistica como el Chi Cuadrado y prueba exacta de Fisher para muestras pequeñas, para conocer la relación entre el parvovirus y la pancreatitis en los 23 perros, arrojando que no hay significancia estadística, en conclusión con los datos actuales, no hay evidencia suficiente para afirmar que exista relación significativa entra ambas enfermedades en esta población específica. Estos hallazgos subrayan la importancia de una investigación más profunda para dilucidar la relación entre ambas enfermedades, así como sus implicaciones diagnósticas y terapéuticas en la práctica clínica veterinaria. Asimismo, resaltan la necesidad de una vigilancia activa y un enfoque integrado en el manejo de estas patologías para mejorar la salud y el bienestar de los pacientes caninos."
Keywords: PANCREATITIS; PARVOVIROSIS CANINA; LIPASA PANCREÁTICA